Exercise in bushfire smoke for high performance athletes: A Position Statement from the Australian Institute of Sport Endorsed by Australasian College of Sport and Exercise Physicians (ACSEP) and Sport Medicine Australia (SMA) - Mooney, M.; Panagodage P., Nirmala K.; Saw, R.; Waddington, G.; Cross, T. J.; Hughes, D. (Journal of Science and Medicine in Sport, 2023)
Objectives: The frequency of bushfires in Australia is increasing and it is expected bushfire smoke will become a more prevalent phenomenon impacting air quality. The objective of this position statement is to provide guidance to the sport sector regarding exercise in air affected by bushfire smoke. Design: This is position statement from the Australian Institute of Sport, based on a narrative review of the literature regarding bushfire smoke and its effects on health and exercise performance. Methods: A narrative review of scientific publications regarding the effects of bushfire smoke on health and exercise performance. Results: Bushfire smoke has negative impacts on health and performance. Athletes exercising at high intensity over a prolonged duration will increase their exposure to air pollutants. Athletes with a history of elevated airway responsiveness are likely to be at increased risk of an adverse response to bushfire smoke exposure. Conclusions: Athletes, coaches, support staff and sport organisations should monitor air quality (PM2.5 concentration) and make appropriate adjustments to training duration and intensity.